Empowering Mothers with Undernutritioned Toddler in Stunting Prevention Efforts - Rohaeti, Ayi Tansah (POLTEKKES KEMENKES BANTEN, 2024)
Stunting is a chronic malnutrition problem caused by a lack of nutritional intake over a long period of time resulting in growth disorders in children, namely the child’s height is lower or shorter than the agestandard. Based in the results of the Indonesian Nutrition Status Study (SSGI) of the ministry of Health, the prevalence of stunting in toddlers is 24,4% in 2021. This means that almost a quarter of Indonesian toddlers are stunted. The national stunting rate shows an improvement, down by 3,3 % from 27,7%. This research aims to identify the knowledge and skills of mothers of undernourished toddlers in an effort to prevent stunting through identifying nutritional status, screening malnourished toddlers using antrhropometric measurements. It is hoped that mothers of malnourished toodlers will be able to increase their knowledge and sills about stunting so that they can invite other mothers to play an active role in preventing stunting.